Answer:
The missing term is 3x
Step-by-step explanation:
Given
-(x - 1) + 5 = 2(x + 3) - _
Required
Find _
For proper identification of the parameters, represent _ with Z
So, the equation becomes
-(x - 1) + 5 = 2(x + 3) - Z
Open bracket (start from the left hand side)
-x + 1 + 5 = 2(x + 3) - Z
-x + 1 + 5 = 2x + 6 - Z
Solve like terms
-x + 6 = 2x + 6 - Z
Subtract 6 from both sides
-x + 6 - 6 = 2x + 6 - 6 - Z
-x = 2x - Z
Subtract 2x from both sides
-x - 2x = 2x - 2x - Z
-3x = -Z
Multiply both sides by -1
-3x * -1 = -Z * -1
3x = Z
Reorder
Z = 3x
Hence, the missing term is 3x
Answer:
39/20 = 1.95
That's my simplified answer
39/20 = 1 19/20
Will this help?
Step-by-step explanation:
This looks like common core which is never straight forward.It seems as though they are asking for the perimeter and not area,since they used feet for the distance around instead of sq.ft.
Answer: An exponential function
Step-by-step explanation:
The data curves upward, slowly becoming closer and closer to a vertical line.
Hope it helps <3